1999
DOI: 10.1051/lait:1999432
|View full text |Cite
|
Sign up to set email alerts
|

Raw milk flora affects composition and quality of Bergkäse. 1. Microbiology and fermentation compounds

Abstract: -Experimental samples of Bergkâse, an Austrian regional hard cheese variety usually made from raw milk, were produced from raw or pasteurised milks in parallel to evaluate the influence of the indigenous microflora on microbiological composition and selected fermentation compounds. Facultatively heterofermentative lactobacilli (FHL) dominated the non-starter flora in cheeses made from raw milk. Viable numbers increased from 1Q4-10 6 cfu-g-' at the age of 1 week to reach their final levelof 10 8 cfu-g! within t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 8 publications
2
16
0
1
Order By: Relevance
“…bulgaricus [42,45,83]. Lactobacilli starters are normally present at levels of 10 9 bacteria/g, contribute to the lactic fermentation, and are involved at the beginning of ripening [70]. For example, in Emmental cheeses, lactobacilli ferment galactose excreted by Streptococcus thermophilus, achieve acidification processes, and contribute to primary proteolysis [31,35,59,74].…”
Section: Cheeses and Milksmentioning
confidence: 99%
See 1 more Smart Citation
“…bulgaricus [42,45,83]. Lactobacilli starters are normally present at levels of 10 9 bacteria/g, contribute to the lactic fermentation, and are involved at the beginning of ripening [70]. For example, in Emmental cheeses, lactobacilli ferment galactose excreted by Streptococcus thermophilus, achieve acidification processes, and contribute to primary proteolysis [31,35,59,74].…”
Section: Cheeses and Milksmentioning
confidence: 99%
“…They originate from the raw milk, and this source was probably more important than the factory environment [17,58]. Differences have been observed between raw milk cheeses and pasteurised or microfiltered milk cheeses [58,70,164]. EliskasesLechner et al [70] found that Bergkäse (Austrian regional cheese) cheeses made from pasteurised milk contained less than one-thousandth the number of facultatively heterofermentative lactobacilli (FHL) present in raw milk cheeses.…”
Section: Cheeses and Milksmentioning
confidence: 99%
“…Also, raw milk may contain wild PAB and NSLAB strains that may promote secondary fermentation [45]. As previously discussed, there is a greater degradation of α s1 -casein in cheese manufactured from raw milk attributed to the raw milk microflora, their associated enzymes [21,23] and also possibly to cathepsin D [41].…”
Section: Milkmentioning
confidence: 98%
“…Cooking temperatures during Emmental manufacture exceed 50°C resulting in little residual coagulant activity [37,90], while cooking temperatures of~36-40°C used in Maasdam/Leerdammer and Jarlsberg manufacture result in higher residual coagulant activities with greater hydrolysis of α s1 -casein or its breakdown products [75]. There is a greater degradation of α s1 -casein in cheese manufactured from raw milk which is attributed to the microflora of the raw milk and their associated enzymes [21,23] and also possibly to the indigenous milk enzyme, cathepsin D [41]. Studies have also suggested a putative role for cathepsin D and for thermophilic lactobacilli [7,33] in the hydrolysis of α s1 -casein during ripening of Swiss-type cheeses.…”
Section: Influence Of Manufacturementioning
confidence: 99%
See 1 more Smart Citation